Which factors predict hospital-acquired late-onset neonatal sepsis?. Issue 4 (August 2008) - Gray, James W
Neonates are one of the highest risk groups of hospitalized patients for sepsis. There is a wide variation in the incidence and microbial causes of late-onset neonatal sepsis, owing to differences in both patient populations and standards of care in the individual neonatal units. Stratification according to risk factors is required to allow the meaningful comparison of infection rates between units. Knowledge of risk factors is also important in order to target interventions on high-risk aspects of neonatal care. Few independent risk factors for late-onset sepsis have been identified, the most common being birth gestational age and parenteral nutrition. Further work is required to validate that these observations can be generalized, and that they could, therefore, be used to stratify infection rates in multicenter surveillance schemes.